Cerebellar ataxias: β‐III spectrin's interactions suggest common pathogenic pathways. (24th April 2016) - Perkins, Emma; Suminaite, Daumante; Jackson, Mandy
Abstract : β‐III spectrin is implicated in a number of cellular processes that are essential for maintaining normal Purkinje cell physiology. Disruption to protein trafficking (1), alterations to intrinsic Purkinje cell firing (2), dendritic architecture (3) and glutamatergic neurotransmission (4) have all been identified as common mechanisms across various SCAs. Abstract: Spinocerebellar ataxias (SCAs) are a genetically heterogeneous group of disorders all characterised by postural abnormalities, motor deficits and cerebellar degeneration. Animal and in vitro models have revealed β‐III spectrin, a cytoskeletal protein present throughout the soma and dendritic tree of cerebellar Purkinje cells, to be required for the maintenance of dendritic architecture and for the trafficking and/or stabilisation of several membrane proteins: ankyrin‐R, cell adhesion molecules, metabotropic glutamate receptor‐1 (mGluR1), voltage‐gated sodium channels (Nav ) and glutamate transporters. This scaffold of interactions connects β‐III spectrin to a wide variety of proteins implicated in the pathology of many SCAs. Heterozygous mutations in the gene encoding β‐III spectrin ( SPTBN2 ) underlie SCA type‐5 whereas homozygous mutations cause spectrin associated autosomal recessive ataxia type‐1 (SPARCA1), an infantile form of ataxia with cognitive impairment. Loss‐of β‐III spectrin function appears to underpin cerebellar dysfunction and degeneration in both diseases resulting in thinner dendrites, excessive dendritic protrusion with loss of planarity, reduced resurgent sodium currents and abnormal glutamatergic neurotransmission. The initial physiological consequences are a decrease in spontaneous activity and excessive excitation, likely to be offsetting each other, but eventually hyperexcitability gives rise to dark cell degeneration and reduced cerebellar output. Similar molecular mechanisms have been implicated for SCA1, 2, 3, 7, 13, 14, 19, 22, 27 and 28, highlighting alterations to intrinsic Purkinje cell activity, dendritic architecture and glutamatergic transmission as possible common mechanisms downstream of various loss‐of‐function primary genetic defects. A key question for future research is whether similar mechanisms underlie progressive cerebellar decline in normal ageing.